Improvement of Corrosion Resistance of Ni-P-Al2O3 Composite Coating by Optimizing Process Parameters Using Potentiodynamic Polarization Test - Gadhari,Prasanna (2014)
Electroless Ni-P based composite coatings are more popular due to their excellent hardness, yield strength, wear resistance, frictional resistance, corrosion resistance, and good lubricity. The present study deals with significance of various coating process parameters on the corrosion behavior of the Ni-P-Al2O3 composite coatings on mild steel substrate. Corrosion behavior of the composite coatings after heat treatment at various annealing temperatures (300 °C, 400 °C, and 500 °C) are investigated by potentiodynamic polarization test using 3.5% NaCl solution. For maximization of corrosion resistance, the electrochemical parameters, corrosion potential (Ecorr) and corrosion current density (Icorr), are optimized using Taguchi based grey relational analysis. For optimization four coating process parameters are considered, namely, concentration of nickel source, concentration of reducing agent, concentration of second phase particles (alumina particles), and annealing temperature, as main design factors. The optimum combinations of the said design factors are obtained from the analysis. Analysis of variance (ANOVA) reveals that the concentration of alumina particles and annealing temperature has the significant influence on the corrosion resistance of the composite coatings. The microstructure of the surface is studied by scanning electron microscopy (SEM) and chemical composition is studied by energy dispersive X-ray analysis (EDX). The X-ray diffraction analysis (XRD) is used to identify the phase transformation behavior of the composite coatings.